Second language acquisition and acculturation: similarities and differences between immigrants and refugees - Jasemi, Ali; Gottardo, Alexandra (Frontiers in Communication, 2023)
Refugees and immigrants differ in their reasons for migration and their criteria for entry into Canada. While economic immigrants migrate to other countries voluntarily, refugees are forced to leave their countries due to fear of death or persecution. Due to the difference in the nature of resettlement, assumptions exist that immigrants and refugees may differ in terms of emotional well-being, social adjustment and acculturation, and second language learning outcomes. To assess these assumptions, this study was conducted on a sample (N = 45) of newcomer Iranian immigrants (Mage = 19.24, SD = 2.06) and refugees (Mage = 23.15, SD = 4.02). The participants completed a series of questionnaires regarding their English language and literacy skills, acculturation, socioeconomic status, emotional well-being, and potential traumatic experiences in the past. This study examined the relationships among these variables for the two groups. The refugees scored lower on variables related to socioeconomic status and had lower English skills than the immigrant group. English word reading and vocabulary were related to second language reading comprehension for immigrants, but only word reading was related to reading comprehension for refugees. The experienced trauma was significantly higher among the refugees. However, the trauma was not a significant predictor for any of the English proficiency skills. Acculturation was related to English reading comprehension, and enculturation was negatively associated with English vocabulary and reading comprehension for refugees but not for immigrants. The findings point to similarities and differences between refugees and immigrants. Recommendations to facilitate resettlement are discussed.